ANALYSIS OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF FLIPPED CLASSROOM LEARNING MODEL IN SCIENCE LEARNING AT SCHOOL - Azizah, Lu'lu (Journal of Learning and Technology in Physics, 2024)
The flipped classroom-based learning model is one of the student-centered learning models to improve learning effectiveness. This learning model reverses student learning time, which usually students come to school to gain knowledge, then it is reversed to be done at home so that time at school is used effectively to discuss material that is not clear and still needs further explanation with students who have previously been equipped with learning material that is the subject of discussion. In this study, the author uses a descriptive qualitative research method that is literature study with secondary data as a source of information to analyze how the application of the flipped classroom learning model in science learning at school and whether this method is able to make the teaching and learning process much more effective and efficient.Keywords: effectiveness; learning model; flipped classroom